Transboundary Haze in Indonesian and Malaysian News Media: Corpus-Assisted Ecolinguistics - Suhandano Suhandano; Arina Isti'anah; Diana Sri Suryani; Roslina Abdul Aziz; Nadhratunnaim Abas; Kamisah Ariffin; Badli Esham Ahmad (Studies in English Language and Education, 2025)
Transboundary haze has gained critical attention from global scholars since its impacts on society, economics, and health are prevalent in mass media. This study aims to examine transboundary haze from an ecolinguistic viewpoint of Indonesian and Malaysian mainstream media. From the data collected, this study; 1) analyses the themes of transboundary haze news in Indonesian and Malaysian media and 2) interprets the themes represented in the discourse ecologically. Using corpus analytical tools provided by Sketch Engine, this study examined the corpuss keywords, collocations, and concordances. Findings show that, despite some identical themes, Indonesian mass media foreground the fires location, mitigation action, and non-human species impacted by the haze. In contrast, Malaysian mass media focuses on the affected areas and health issues. Both media involved similar strategies to frame the government as the responsible agent for mitigating the fires and haze. Ecologically, the discourse of transboundary haze in Indonesian and Malaysian mass media is ambivalent. In Indonesian media, transboundary haze is regarded as a disaster rather than a conflict due to human activities related to land clearings, whereas Malaysian media captures transboundary haze as a health and pollution issue. The ambivalent discourse is proven by the lack of human activities that cause transboundary haze, even though the media advocates for environmental and health issues as prevalent themes in news broadcasts. Ecologically, this study recommends mass media to emphasise the anthropocentric causes of transboundary haze to raise public awareness about human activities and their environmental consequences.